2020
DOI: 10.1097/md.0000000000023063
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 diversity and compartmentalization in urine, semen, and blood

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A study on SRLVs compartmentalization performed to date revealed the presence of different viral sequences in the blood, mammary gland, lungs, and central nervous system tissue in clinically affected sheep [6] and in the colostrum and peripheral blood of goats [5,8]. Similarly, compartmentalization has been well documented in the brain, cerebrospinal fluid, and genital tract, as well as in the gut, lung, liver, kidney, and breast milk of patients infected with HIV-1 [34][35][36][37][38]. In the current study, SRLVs sequences from PBLs and milk epithelial cells were genetically similar suggesting an equilibrium of virus between these compartments.…”
Section: Discussionmentioning
confidence: 97%
“…A study on SRLVs compartmentalization performed to date revealed the presence of different viral sequences in the blood, mammary gland, lungs, and central nervous system tissue in clinically affected sheep [6] and in the colostrum and peripheral blood of goats [5,8]. Similarly, compartmentalization has been well documented in the brain, cerebrospinal fluid, and genital tract, as well as in the gut, lung, liver, kidney, and breast milk of patients infected with HIV-1 [34][35][36][37][38]. In the current study, SRLVs sequences from PBLs and milk epithelial cells were genetically similar suggesting an equilibrium of virus between these compartments.…”
Section: Discussionmentioning
confidence: 97%
“…In the early 1980s, the first cases of Acquired Immunodeficiency Syndrome (AIDS) were recorded around the world, and innumerable reports drew the attention of the scientific and medical community to the high mortality rates in the patients affected by this new pathogen [1,2]. Initially, this epidemic was associated with specific groups, such as men that have sex with men, drug users, and recipients of blood transfusions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite multicenter pilot studies reported that overall patient and graft survival in HIV+ donor to HIV+ recipients were excellent [13][14][15], the main concern about HIV/HIV transplantation is the possibility of donor derived HIV superinfection of the recipients. Kidneys and livers are considered a reservoir of HIV infection: compartimentalized HIV replication has been demonstrated in kidneys, with site-specific viral variants in urine segregating from those present in plasma [16,17], whereas livers may harbor latently infected cells in subjects under effective antiviral treatment [18]. Ultradeep sequencing (UDS) of viral quasispecies is a poweful tool to investigate variant mixture among infected individuals and has been used to trace transmission chains and cluster identification [19,20].…”
Section: Introductionmentioning
confidence: 99%